2006
DOI: 10.1248/bpb.29.2295
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Alkaline Protease Can Facilitate Siderophore-Mediated Iron-Uptake via the Proteolytic Cleavage of Transferrins

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen which is frequently isolated from clinical specimens obtained from burns, surface wounds, the urinary tract, ear and eye infections, and the lungs of patients with cystic fibrosis. 1) P. aeruginosa secretes many extracellular proteins, and of these, several proteases including alkaline protease (AprA) and elastase (LasB) are known to play important roles in the pathogenesis of human infections caused by P. aeruginosa. 2,3)In response to iron deprivation, P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Planktonic AES‐2 showed enhanced expression of iron acquisition genes pyoverdine pvdA(PA2386 ) and pyoverdine synthetase pvdF(PA2396 ) (22.9 × and 5.4 × , respectively, Table 1) compared with infrequent clones; however, expression was significantly downregulated (−6.3 × and −8.8 × ) in AES‐2 biofilms, which showed expression similar to infrequent clone biofilms. Alkaline protease expression facilitates siderophore‐mediated iron uptake by P. aeruginosa (Kim et al , 2006); thus, enhanced expression of pyoverdine in planktonic culture may be due to the increased alkaline protease activity. It is possible that the infrequent clones utilize a different sequestration pathway to AES‐2, because they had significantly higher expression (8.3 × ) than AES‐2 of the B subunit of bacterioferritin, bfrB(PA3531) , another major iron‐storage protein in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Planktonic AES‐2 showed enhanced expression of iron acquisition genes pyoverdine pvdA(PA2386 ) and pyoverdine synthetase pvdF(PA2396 ) (22.9 × and 5.4 × , respectively, Table 1) compared with infrequent clones; however, expression was significantly downregulated (−6.3 × and −8.8 × ) in AES‐2 biofilms, which showed expression similar to infrequent clone biofilms. Alkaline protease expression facilitates siderophore‐mediated iron uptake by P. aeruginosa (Kim et al , 2006); thus, enhanced expression of pyoverdine in planktonic culture may be due to the increased alkaline protease activity. It is possible that the infrequent clones utilize a different sequestration pathway to AES‐2, because they had significantly higher expression (8.3 × ) than AES‐2 of the B subunit of bacterioferritin, bfrB(PA3531) , another major iron‐storage protein in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa causes severe tissue damage by the expression of the alkaline protease AprA, especially in CF patients where it has been associated with increased infectivity and virulence, suggesting a role in processes related to bacterial colonization and/or exacerbation in the CF lung (Burke et al, 1991 ; Kim et al, 2006 ). Our findings suggested that in mixed infections S. maltophilia might indirectly facilitate the onset of PEs in CF patients by inducing increased proteolytic activity in P. aeruginosa , probably via a Las/RhI independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa pyoverdine and pyochelin can displace iron from transferrin (Takase et al, 2000). P. aeruginosa also has the ability to release iron from transferrin using elastase (LasB; Wolz et al, 1994), the alkaline protease AprA (Kim et al, 2006) and the endoprotease PrpL (Wilderman et al, 2001). PrpL can also hydrolyse lactoferrin, in addition to other extracellular host proteins, leading to tissue damage and further contributing to the infection process (Wilderman et al, 2001).…”
Section: Iron Acquisition From Host Iron-binding Proteinsmentioning
confidence: 99%